Travailleurs-euses, étudiant-es : Même combat ! (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2013)
In the wake of the Québec student movement, graduate students of the 2012-2013 executive team for the Teaching Assistants’ Unit of the Association of Graduate Students Employed at McGill (AGSEM) reflect on their individual backgrounds and motivations for pursuing union work. With various opportunities for employment on and off campus, what compels academic workers to serve their union; to become accountable to a diverse and growing membership, and to challenge the very institutional machinery upon which our careers can depend? As students, educators, activists, and workers, we reflect on these questions in considering how we have come to the union, why we have become advocates for workers’ rights, and the kinds of challenges and successes we experienced.